Face-to-face health professional contact for postpartum women: A systematic review. Issue 6 (November 2020) - Brodribb, Wendy; Hawley, Glenda; Mitchell, Ben; Mathews, Ann; Zakarija-Grković, Irena
Abstract: The postpartum period is a time when physical, psychological and social changes occur. Health professional contact in the first month following birth may contribute to a smoother transition, help prevent and manage infant and maternal complications and reduce health systems' expenditure. The aim of this systematic review was to assess the effect of face-to-face health professional contact with postpartum women within the first four weeks following hospital discharge on maternal and infant health outcomes. Fifteen controlled trial reports that included 8332 women were retrieved after searching databases and reference lists of relevant trials and reviews. Although the evidence was of moderate or low quality and the effect size was small, this review suggests that at least one health professional contact within the first 4 weeks postpartum has the potential to reduce the number of women who stop breastfeeding within the first 4–6 weeks postpartum (Risk Ratio 0.86 (95% Confidence Interval 0.75–0.99)) and the number of women who cease exclusive breastfeeding by 4–6 weeks (Risk Ratio 0.84 (95% Confidence Interval 0.71–0.99)) and 6 months (Risk Ratio 0.88 (95% Confidence Interval 0.81–0.96). There was no evidence that one form of health professional contact was superior to any other. There was insufficient evidence to show that health professional contact in the first month postpartum, at a routine or universal level, had an impact on other aspects of maternal and infant health, including non-urgent or urgent use of health services.